Lensed or not lensed: determining lensing magnifications for binary neutron star mergers from a single detection. Issue 4 (23rd May 2020) - Pang, Peter T H; Hannuksela, Otto A; Dietrich, Tim; Pagano, Giulia; Harry, Ian W
ABSTRACT: Advanced LIGO and Advanced Virgo could observe the first lensed gravitational wave sources in the coming years, while the future Einstein Telescope could observe hundreds of lensed events. It is, therefore, crucial to develop methodologies to distinguish between lensed from unlensed gravitational-wave observations. A lensed signal not identified as such will lead to biases during the interpretation of the source. In particular, sources will appear to have intrinsically higher masses. No robust method currently exists to distinguish between the magnification bias caused by lensing and intrinsically high-mass sources. In this work, we show how to recognize lensed and unlensed binary neutron star systems through the measurement of their tidal effects for highly magnified sources as a proof-of-principle. The proposed method could be used to identify lensed binary neutron stars that are the chief candidate for lensing cosmography studies. We apply our method on GW190425, finding no evidence in favour of lensing, mainly due to the poor measurement of the event's tidal effects. However, we expect that future detections with better tidal measurements can yield better constraints.